Allelopathic inhibition of harmful algae by mangrove leaf extracts under contrasting habitats and algal densities - Tao Lang; Haichao Zhou; Yuanyue Li; Nora Fung-Yee Tam; Min Pan; Fred Wang-Fat Lee; Steven Jing-Liang Xu (Marine Pollution Bulletin, 2026)

Carboxylic acid leaching for rare earth element recovery from coal fly ash after pretreatment: a review - Steven Ghambi; Lingmei Ren; Jinhe Pan; Lei Zhang; Shulan Shi; Changchun Zhou (Minerals Engineering, 2026)

Visible light-driven photocatalytic self-fenton systems with β-ketoenamine covalent organic frameworks for rapid aquaculture pathogen inactivation - Yik Tung Sham; Min Pan; Steven Jing-Liang Xu; Tsz Wai Ng; Jennie Yan Ning Yu; Qiuxiang Xu; Zhangna Wang (Journal of Environmental Chemical Engineering, 2026)

Integrative metabolomic profiling reveals comparable nutritional quality and diminished sensory qualities in Porphyra yezoensis from January versus April harvest - Yi Ding; Xiran Huang; Tianxi Zhang; Saikun Pan; Liangliang Qian; Suryoprabowo Steven; Wenbin Wang (Food Chemistry, 2026)

Happy Healthy Homes Virtual Intervention Improved Rural Family Child Care Home Provider Mealtimes: Partial and Sustained Effects - Divya Patel; Dipti A. Dev; Steven Pan; Bethany Williams; Alicia L. Salvatore; Susan B. Sisson (Journal of Nutrition Education and Behavior, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Differential regulation of root iron plaque formation in a mangrove species, Kandelia obovata by biodegradable and conventional nanoplastics: Evidence from interfacial interactions, microbial communities, and redox conditions - Ming Li; Jie Gao; Nora Fung-Yee Tam; Haichao Zhou; Min Pan; Fred Wang-Fat Lee; Steven Jing-Liang Xu; Jian Liu; Kaixuan Deng; Peng Zheng; Cheng Ye; Xinran Ke; et al. (Environmental Pollution, 2026)

Dual Mechanisms of Nanobubble Technology for Plant Growth Enhancement and Soil Remediation Amid Challenges - Yik Tung Sham; Min Pan; Liwen Luo; Kenrick Chun Kiu Ho; Jennie Yan Ning Yu; Steven Jingliang Xu (Water, Air, & Soil Pollution, 2026)

Plants experience reduced a negative plant-soil feedback due to mycorrhizal fungi change with neighbors in a harsh environment - Guo Pinglin; Peng Fei; Xue Xian; Pan Jing; You Quangang; Huang Cuihua; Zhou Jun; Carly Stevens (Biology and Fertility of Soils, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Preface: Advances in freshwater algal ecology - Yangdong Pan; Steven T. Rier; Kalina Manoylov (Hydrobiologia, 2025)

Buckling forces and the wavy folds between pleural epithelial cells - Joseph Sutlive; Betty S. Liu; Stacey A. Kwan; Jennifer M. Pan; Kun Gou; Rongguang Xu; Ali B. Ali; Hassan A. Khalil; Maximilian Ackermann; Zi Chen; Steven J. Mentzer (BioSystems, 2024)

Soil legacy nutrients contribute to the decreasing stoichiometric ratio of N and P loading from the Mississippi River Basin - Zihao Bian; Hanqin Tian; Shufen Pan; Hao Shi; Chaoqun Lu; Christopher Anderson; Wei‐Jun Cai; Charles S. Hopkinson; Dubravko Justic; Latif Kalin; Steven Lohrenz; Steven McNulty; et al. (Global Change Biology, 2023)
Human‐induced nitrogen–phosphorus (N, P) imbalance in terrestrial ecosystems can lead to disproportionate N and P loading to aquatic ecosystems, subsequently shifting the elemental ratio in estuaries and coastal oceans and impacting both the structure and functioning of aquatic ecosystems. The N:P ratio of nutrient loading to the Gulf of Mexico from the Mississippi River Basin increased before the late 1980s driven by the enhanced usage of N fertilizer over P fertilizer, whereafter the N:P loading ratio started to decrease although the N:P ratio of fertilizer application did not exhibit a similar trend. Here, we hypothesize that different release rates of soil legacy nutrients might contribute to the decreasing N:P loading ratio. Our study used a data‐model integration framework to evaluate N and P dynamics and the potential for long‐term accumulation or release of internal soil nutrient legacy stores to alter the ratio of N and P transported down the rivers. We show that the longer residence time of P in terrestrial ecosystems results in a much slower release of P to coastal oceans than N. If contemporary nutrient sources were reduced or suspended, P loading sustained by soil legacy P would decrease much slower than that of N, causing a decrease in the N and P loading ratio. The longer residence time of P in terrestrial ecosystems and the increasingly important role of soil legacy nutrients as a loading source may explain the decreasing N:P loading ratio in the Mississippi River Basin. Our study underscores a promising prospect for N loading control and the urgency to integrate soil P legacy into sustainable nutrient management strategies for aquatic ecosystem health and water security.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Prospective evaluation of functional brain activity and oxidative damage in breast cancer: changes in task-induced deactivation during a working memory task - James C. Root; Denise Pergolizzi; Hong Pan; Irene Orlow; Steven D. Passik; David Silbersweig; Emily Stern; Tim A. Ahles (Brain Imaging and Behavior, 2021)

Episodic memory for visual scenes suggests compensatory brain activity in breast cancer patients: a prospective longitudinal fMRI study - Denise Pergolizzi; James C. Root; Hong Pan; David Silbersweig; Emily Stern; Steven D. Passik; Tim A. Ahles (Brain Imaging and Behavior, 2019)

MicroRNA-942 mediates hepatic stellate cell activation by regulating BAMBI expression in human liver fibrosis - Le Tao; Dongying Xue; Dongxiao Shen; Wenting Ma; Jie Zhang; Xuefei Wang; Wei Zhang; Liu Wu; Kai Pan; Yanqin Yang; Zeribe C. Nwosu; Steven Dooley; et al. (Archives of Toxicology, 2018)

Functioning of Coastal River-Dominated Ecosystems and Implications for Oil Spill Response: From Observations to Mechanisms and Models - Adam Greer; Alan Shiller; Eileen Hofmann; Jerry Wiggert; Sally Warner; Sabrina Parra; Chudong Pan; Jeffrey Book; DongJoo Joung; Steven Dykstra; Jeffrey Krause; Brian Dzwonkowski; et al. (Oceanography, 2018)

Reconciling multiple impacts of nitrogen enrichment on soil carbon: plant, microbial and geochemical controls - Chenglong Ye; Dima Chen; Steven J. Hall; Shang Pan; Xuebin Yan; Tongshuo Bai; Hui Guo; Yi Zhang; Yongfei Bai; Shuijin Hu (Ecology Letters, 2018)
Impacts of reactive nitrogen (N) inputs on ecosystem carbon (C) dynamics are highly variable, and the underlying mechanisms remain unclear. Here, we proposed a new conceptual framework that integrates plant, microbial and geochemical mechanisms to reconcile diverse and contrasting impacts of N on soil C. This framework was tested using long‐term N enrichment and acid addition experiments in a Mongolian steppe grassland. Distinct mechanisms could explain effects of N on particulate and mineral‐associated soil C pools, potentially explaining discrepancies among previous N addition studies. While plant production predominated particulate C changes, N‐induced soil acidification strongly affected mineral‐associated C through decreased microbial growth and pH‐sensitive associations between iron and aluminium minerals and C. Our findings suggest that effects of N‐induced acidification on microbial respiration and geochemical properties should be included in Earth system models that predict ecosystem C budgets under future N deposition/input scenarios.

North American terrestrial CO2 uptake largely offset by CH4 and N2O emissions: toward a full accounting of the greenhouse gas budget - Hanqin Tian; Guangsheng Chen; Chaoqun Lu; Xiaofeng Xu; Daniel J. Hayes; Wei Ren; Shufen Pan; Deborah N. Huntzinger; Steven C. Wofsy (Climatic Change, 2015)

Investigation of Vietnamese plants for potential anticancer agents - Lynette Bueno Pérez; Patrick C. Still; C. Benjamin Naman; Yulin Ren; Li Pan; Hee-Byung Chai; Esperanza J. Carcache de Blanco; Tran Ngoc Ninh; Bui Van Thanh; Steven M. Swanson; Djaja D. Soejarto; A. Douglas Kinghorn (Phytochemistry Reviews, 2014)

Tonoplast Lipid Composition and Proton Pump of Pineapple Fruit During Low-Temperature Storage and Blackheart Development - Yuchan Zhou; Xiaoping Pan; Hongxia Qu; Steven J. R. Underhill (The Journal of Membrane Biology, 2014)

Century-Scale Responses of Ecosystem Carbon Storage and Flux to Multiple Environmental Changes in the Southern United States - Hanqin Tian; Guangsheng Chen; Chi Zhang; Mingliang Liu; Ge Sun; Arthur Chappelka; Wei Ren; Xiaofeng Xu; Chaoqun Lu; Shufen Pan; Hua Chen; Dafeng Hui; et al. (Ecosystems, 2012)

Soil microbial activity, aggregation and nutrient responses to straw pulping liquor in corn cropping - C. Xiao; R. Stevens; M. Fauci; R. Bolton; M. Lewis; W. T. McKean; D. F. Bezdicek; W. L. Pan (Biology and Fertility of Soils, 2007)

Modeled responses of terrestrial ecosystems to elevated atmospheric CO 2 : a comparison of simulations by the biogeochemistry models of the Vegetation/Ecosystem Modeling and Analysis Project (VEMAP) - Yude Pan; Jerry M. Melillo; A. David McGuire; David W. Kicklighter; Louis F. Pitelka; Kathy Hibbard; Lars L. Pierce; Steven W. Running; Dennis S. Ojima; William J. Parton; David S. Schimel (Oecologia, 1998)